Circulations, spatial organisation and development in West Africa: the Tambacounda region in Senegal - (:unkn) unknown (My University, 2003)
Africa experiences intensive, old and new continental mobility in spite of a marginal situation in the world trade. Mobility is imperative in the contemporary Senegal. The shapes, the targets and the causes of mobility are becoming various. The region of Tambacounda is rural, has a low density of population and is badly linked to the national centre of economic and social life. In this region, traffics show off two phenomenons. On the one hand, the traffics concentrate onto the main road to Dakar. This testifies that the regional development depends on national structures. On the other hand, local poles and networks, based upon local dynamism, are raising. Those both phenomenons show off a transition for Senegal. The country is changing its frames for development and organisation of space.
Keywords: African Research